Efficiency optimization of organic light-emitting diodes - Liu, Shuwei (2015)
Interest in Organic light-emitting diode (OLEO) technology was extensive lately, because of the unique advantages compared to its inorganic counterpart and other technologies. With extensive research of more than two decades, OLEO has advanced from pure laboratory research and stepped into the commercial world, however, due to current limitation in efficiency, yield and cost, OLEO technology has still a long way to go to be a dominant force in display and lighting market.